Anatomical, functional, physiological and behavioural aspects of the development of mastication in early childhood - Benjamin J. D. Le Révérend; Lisa Edelson; Chrystel Loret (2013)
Mastication efficiency is defined as the efficiency of crushing food between the teeth and manipulating the resulting particles to form a swallowable food bolus. It is dependent on the orofacial anatomical features of the subject, the coordination of these anatomical features and the consistency of the food used during testing. Different measures have been used to indirectly quantify mastication efficiency as a function of children's age such as observations, food bolus characterisation, muscle activity measurement and jaw movement tracking. In the present review, we aim to describe the changes in the oral physiology (e.g. bone and muscle structure, teeth and soft tissues) of children and how these changes are associated with mastication abilities. We also review previous work on the effect of food consistency on children's mastication abilities and on their level of texture acceptance. The lack of reference foods and differences in testing methodologies across different studies do not allow us to draw conclusions about (1) the age at which mastication efficiency reaches maturity and (2) the effect of food consistency on the establishment of mature mastication efficiency. The effect of food consistency on the development of children's mastication efficiency has not been tested widely. However, both human and animal studies have reported the effect of food consistency on orofacial development, suggesting that a diet with harder textures enhances bone and muscle growth, which could indirectly lead to better mastication efficiency. Finally, it was also reported that (1) children are more likely to accept textures that they are able to manipulate and (2) early exposure to a range of textures facilitates the acceptance of foods of various textures later on. Recommending products well adapted to children's mastication during weaning could facilitate their acceptance of new textures and support the development of healthy eating habits.